2004
DOI: 10.1007/s00330-004-2447-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of IPA in HIV: the role of the chest X-ray and radiologist

Abstract: The role of clinical information and chest film for the discrimination between invasive pulmonary aspergillosis (IPA) and its differential diagnoses in human immunodeficiency virus (HIV) infection was studied. The diagnostic performance of clinical information and chest film alone and in combination was studied for eight internists and eight radiologists with regular exposure to IPA patients. The multicenter case sample consisted of 25 patients with proven IPA and 25 with other pulmonary diseases typical for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
10
0
2
Order By: Relevance
“…The development of consolidations with cavities has been also observed in numerous cases ( Table 3). The air crescent sign -which is noted in up to 93% among certain groups of immunocompromised patients with IA -is less frequently among HIVinfected patients [21,23]. A proposed explanation is that this sign is associated with the rapid recovery from severe immunosuppression, a phenomenon that is move slow usual among AIDS patients.…”
Section: Clinical Manifestationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The development of consolidations with cavities has been also observed in numerous cases ( Table 3). The air crescent sign -which is noted in up to 93% among certain groups of immunocompromised patients with IA -is less frequently among HIVinfected patients [21,23]. A proposed explanation is that this sign is associated with the rapid recovery from severe immunosuppression, a phenomenon that is move slow usual among AIDS patients.…”
Section: Clinical Manifestationsmentioning
confidence: 98%
“…Autopsy studies have shown that the ante mortem diagnosis of AIDS-associated IA is often underestimated. In vivo diagnosis is misunderstood since nonspecific symptoms often mask multiple infections [23] (Table 5). EIA for galactomannan detection has been validated in animal models and in patients as a surrogate marker for the detection of IA [25].…”
Section: Diagnosismentioning
confidence: 99%
“…Consolidation or mass is the most common CT finding of IPA in solid organ transplantation (SOT) recipients and presence of small cavities may be associated with favorable prognosis [48] . Zaspel et al [49] identified characteristic radiological appearance of IPA in HIV patients as nodules (92%), cavitations (75%), air crescent sign (33%) or subpleural infarctions (17%). Thick-walled cavitary lesions were demonstrated as a late finding in late-stage AIDS with a CD4 cell count of < 5/mm 3 [50] .…”
Section: Airway Invasive Aspergillosis Is An Uncommon Invasive Diseasmentioning
confidence: 99%
“…The main drawback of CXR is a limited sensitivity in the detection of early infection in these patients, whose immune reactivity is poorer and delayed compared with immunocompetent ones [10][11][12][13][14]. To our knowledge, few authors have investigated the role of the knowledge of clinical and laboratory data in CXR evaluation of patients with suspected pulmonary infection, with discordant results [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In tali pazienti, la cui reattività al processo infettivo è ridotta e ritardata rispetto ai soggetti immunocompetenti, il principale limite della radiografia del torace è la limitata sensibilità nell'identificazione precoce di reperti patologici [10][11][12][13][14]. A nostra conoscenza, pochi autori hanno indagato il ruolo della conoscenza delle condizioni cliniche e dei dati laboratoristici di questi pazienti nell'interpretazione della radiografia del torace eseguita nel sospetto di polmonite, con risultati peraltro discordanti [15][16][17].…”
Section: Introductionunclassified